Of Moths and Motor Cars: Vital Circulation and the ‘Meeting-Text’ in Virginia Woolf’s ‘The Death of the Moth’ and ‘Evening over Sussex’ - Xavier Le Brun (Études Britanniques Contemporaines, 2025)
Starting from an examination of vital energy in two essays by Virginia Woolf—‘The Death of the Moth’ and ‘Evening over Sussex: Reflections in a Motor Car’, both initially published in the posthumous collection The Death of the Moth and Other Essays (1942)—this article establishes that ‘life’ is conceived by Woolf as a process of circulation and exchange, extending beyond the diegetic level to embrace the relationship between reader and narrative voice. What Woolf seeks to set up in ‘The Death of the Moth’, ‘Evening over Sussex’ and other short writings fostering a sense of intimacy with their narrator, is a form of textual coexistence which I propose to refer to as ‘meeting-texts’. Relying on the pronoun ‘one’ as well as on condensed chronotopes to generate joint reader-narrator experience, the subgenre of the ‘meeting-text’ aims at ‘convey[ing] what one saw . . . so that another person [can] share it’ (Woolf, ‘Evening over Sussex’).